1998
DOI: 10.1126/science.280.5362.427
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tract as a Major Site of CD4 + T Cell Depletion and Viral Replication in SIV Infection

Abstract: Human and simian immunodeficiency virus (HIV and SIV) replicate optimally in activated memory CD4(+) T cells, a cell type that is abundant in the intestine. SIV infection of rhesus monkeys resulted in profound and selective depletion of CD4+ T cells in the intestine within days of infection, before any such changes in peripheral lymphoid tissues. The loss of CD4+ T cells in the intestine occurred coincident with productive infection of large numbers of mononuclear cells at this site. The intestine appears to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

61
1,084
6
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,292 publications
(1,165 citation statements)
references
References 11 publications
61
1,084
6
5
Order By: Relevance
“…Lymphocytes from the intestine and mesenteric LN were isolated as described earlier [12,25]. In brief, epithelial cells were separated from intestinal pieces using serial incubations with EDTA.…”
Section: Isolation Of Lymphocytes From Intestine and Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphocytes from the intestine and mesenteric LN were isolated as described earlier [12,25]. In brief, epithelial cells were separated from intestinal pieces using serial incubations with EDTA.…”
Section: Isolation Of Lymphocytes From Intestine and Lymph Nodesmentioning
confidence: 99%
“…Intestinal effector lymphoid tissues (i.e. lamina propria) have been shown to be the major site of viral replication and CD4 + T cell depletion in primary HIV and SIV infection [7,[25][26][27][28]. Our earlier studies demonstrated that DP T cells co-expressing CCR5 in the intestine were rapidly eliminated in primary SIV infection.…”
mentioning
confidence: 99%
“…4 Accumulating data also indicate that gut-associated lymphoid tissue (GALT), which contains inductive sites, Peyer's patches and mesenteric (Mes) LNs, and effectors sites located within lamina propria and epithelium of the intestinal wall, is also an early and predominant tissue site of viral replication and may be a reservoir for HIV/SIV. 5,6 Because T cells from the GALT are required to maintain a state of immunological tolerance toward a myriad of dietary and resident bacterial antigens, the chronic exposure of HIV/ SIV-specific antigens could have an impact on the capacity of CD8 þ T cells to control viral replication in the GALT.Addressing these complex pathways in HIV-1 infected patients is limited by the access to internal tissue biopsies, and therefore macaques provide a useful model to address and explore these fundamental questions of the anatomical viral reservoirs and the dynamics of effector cells that control viral replication. We examined organs from 12 monkeys (controllers versus non-controllers), sampling peripheral blood, Ing and Mes LNs, spleen, jejunum, colon, ileum, lung, kidney and liver.…”
mentioning
confidence: 99%
“…4 Accumulating data also indicate that gut-associated lymphoid tissue (GALT), which contains inductive sites, Peyer's patches and mesenteric (Mes) LNs, and effectors sites located within lamina propria and epithelium of the intestinal wall, is also an early and predominant tissue site of viral replication and may be a reservoir for HIV/SIV. 5,6 Because T cells from the GALT are required to maintain a state of immunological tolerance toward a myriad of dietary and resident bacterial antigens, the chronic exposure of HIV/ SIV-specific antigens could have an impact on the capacity of CD8 þ T cells to control viral replication in the GALT.…”
mentioning
confidence: 99%
“…Specifically, within days to up to three weeks of initial exposure, there is a burst in viremia that can reach levels exceeding one million copies/ml [1]. This high magnitude of viral titer accelerates the dissemination and seeding of HIV to various tissue compartment, most significantly in gut-associated mucosal tissue [2][3][4]. Tissue dissemination of HIV is accompanied by direct HIV-mediated cytopathic effects on CD4+ memory T cells, leading to their loss, as was evident in acute Simian Immunodeficiency Virus (SIV) infection [5].…”
Section: Introductionmentioning
confidence: 99%